Pervasive refusal syndrome in child asylum seekers on Nauru. (October 2020) - Newman, Louise; O'Connor, Beth; Reynolds, Vernon; Newhouse, George
Objectives: Between 2013 and 2019, an estimated 200 children seeking asylum in Australia were detained on the island of Nauru. In 2018, 15 of these children developed the rare and life-threatening pervasive refusal syndrome (PRS). This paper describes the PRS case cluster, the complexities faced by clinicians managing these cases, and the lessons that can be learned from this outbreak. Conclusions: The emergence of PRS on Nauru highlighted the risks of long-term detention of children in settings that are unable to meet their physical and psycho-social needs. The case cluster also underscored (a) the difficulties faced by doctors working in conditions where their medical and legal obligations may be in direct conflict, and (b) the role of clinicians in patient advocacy.